Determinants of specialty rice adoption by smallholder farmers in the Red River Delta of Vietnam - Thai Thuy Pham; Dao The Anh; Ludwig Theuvsen (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2017)
This study addresses factors influencing the adoption of specialty rice variety among smallholder farmers in Vietnam. We used a sample of 336 farmers from the Red River Delta who were interviewed between October and December 2014. We follow the adoption behavior model based on the utility maximization criterion and adopt a two-step approach, starting with a Probit model for determinants of specialty rice adoption before analyzing the intensity of adoption using a Tobit model. Overall, 50% of the probability of specialty rice adoption is explained by the selected independent variables such as: cultivated land, experience in growing rice, and network size. Tobit model estimates show that group membership (such as in agricultural cooperatives, farmer's union, etc.) and possession of a two-wheel-tractor increase the share of land allocation to specialty rice production by 3.4% and 7.8% respectively. Based on the findings manifold social and political implications will be derived.
Keywords: O30; Q16; R20; 330; Specialty Rice; Adoption; Smallholder Farmers; Network Size; Red River Delta